ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2024 - Barus, Juni Kristin (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
The Hospital Management Information System (HMIS) is an information technology system that processes and integrates the entire hospital service process flow, to support patient service management and health information management in hospitals. Good use of HMIS is very necessary to support the smooth service process in a hospital. This research aims to find out how to analyze factors related to the use of the hospital management information system (HMIS) at the sembiring deli tua general hospital based on a perspective of task characteristic, technology characteristic and task technology fit. This research is a quantitative research, with analytical observational methods, cross-sectional approach and uses a questionnaire as a data collection instrument. The research sample consisted of 82 HMIS users determined using the slovin formula. The questionnaire used was tested for validity & reliability on 30 people outside the sample, namely officers directly related to SIMRS at Grandmed General Hospital. The results of the Kolmogorov Smirnov normality test inform that the data is normally distributed, therefore the analysis method used was the pearson product moment test. Based on the test results, it is known that task characteristic have a p-value of 0,001, technology characteristic have a p-value of 0,001 and task technology fit have a p-value of 0.000. This proves that all variables have a positive and significant relationship with the HMIS utilization, because the p-value obtained is <0.005. So it can be concluded that the higher the level of task characteristics, technology characteristic and task technology fit, the higher the level of HMIS utilization at the Sembiring Deli Tua general hospital.